2014
DOI: 10.1016/j.envres.2014.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Environmental arsenic epidemiology in the Mekong river basin of Cambodia

Abstract: a b s t r a c tWe investigated relationship of arsenicosis symptoms with total blood arsenic (BAs) and serum albumin (SAlb) of residents in the Mekong River basin of Cambodia. We found that arsenicosis patients had significantly higher BAs and lower SAlb than asymptomatic villagers (Mann-Whitney U test, po 0.01). Arsenicosis symptoms were found to be 76.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Along with the hair samples from KT, the groundwater samples from KT also yielded the lowest levels of Fe, As, Mo, and Ba among the four areas. It has been observed that the level of metals in groundwater is not the only factor affecting the accumulation of metals in biomarkers; other important factors include age, gender, individual susceptibility, period of groundwater consumption and amount of daily groundwater consumption [ 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Along with the hair samples from KT, the groundwater samples from KT also yielded the lowest levels of Fe, As, Mo, and Ba among the four areas. It has been observed that the level of metals in groundwater is not the only factor affecting the accumulation of metals in biomarkers; other important factors include age, gender, individual susceptibility, period of groundwater consumption and amount of daily groundwater consumption [ 18 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, about 1.2% of the whole population in this study was found with urinary As higher than 700 ng·mg −1 . An epidemiological study of environmental As exposure in Kandal Province has shown that the urinary As levels in both asymptomatic (73.04 ± 52.24 ng·mg −1 ) and arsenicosis patients (78.74 ± 69.84 ng·mg −1 ) were not significantly different [ 18 ]. Noting that the levels of urinary As from subjects in KT village consuming As-free groundwater (0.54–8.36 μg·L −1 ) were not statistically different from those of subjects consuming As-enriched groundwater, the results of urinary As obtained from this present study could not solely be used to indicate the level of As exposure or predict the development of individual As health impacts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations